Mekanisme Penetapan Mustahik Zakat Produktif Dalam Rangka Peningkatan Ekonomi Masyarakat di BAZNAS Kota Solok - Rasmi Hayati (Institute of Research and Community Service Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
This study analyzes the mechanism that is implemented at BAZNAS Solok City in determining productive zakat mustahik. The results of the study state that the mechanism implemented at BAZNAS Solok City in determining productive mustahik zakat begins with the provision of application and registration forms, verification, interviews, field surveys and deliberations on determining mustahik (plenary meeting), after determining mustahik then distribution or delivery of capital assistance is carried out productive economic zakat business